COHORT-BASED GRAMMAR TEACHING MODEL DEVELOPMENT IN STRUCTURE SECTION OF TOEFL AT SEKOLAH TINGGI ILMU MANAJEMEN SUKMA MEDAN - Hidayat Hidayat; Busmin Gurning; Rahmad Husein (LINGUISTIK TERAPAN, 2018)
This research makes use of Research and Development method in which a teaching model is developed to teaching grammar in the form of multiple-choice questions. It is Cohort-based Grammar Teaching Model that is developed. In the development of this teaching model, fifty students took part in. The research was conducted at Sekolah Tinggi Ilmu Manajemen Sukma Medan on jalan Sakti Lubis no. 80. To figure out what teaching model which the students need, questionaire was disseminated. In analyzing the available data from the instrument, questionaire inspired by Guttman Scale was made with numerous modifications in statements and questions.The analysis reveals that the participants require an intersting and fun grammar teaching model; easy to understand and more efective; quick problem-solving, time-saving  and target-oriented.  Due to this reason, eventually, Cohort-based Grammar Teaching Model is not mediocrewhere it is capable of alternating grammar problem for multiple-choice question in structure part of the TOEFL in a relative instant high result way.Keywords: Research and Development, Teaching Grammar, Multiple-choice question, Cohort